Penafsiran Hukum Pasal 87 Ayat (1) Huruf D PKPU Nomor 10 Tahun 2023 Tentang Tindak Pidana Lainnya Terhadap Hak Konstitusional Warga Negara Menjadi Calon Anggota Legislatif - Mulyani, Basri (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2024)
Election process disputes include disputes between Election Participants and disputes between Election Participants and Election Organizers as a result of the issuance of General Election Commission decisions, Provincial General Election Commission decisions, and Regency/City General Election Commission decisions. There are so many disputes that are submitted to the General Election Supervisory Body at every level from the stage of determining the Temporary Candidate List until the Permanent Candidate List has been determined, such as the adjudication dispute that occurred at the West Nusa Tenggara Province General Election Supervisory Body over the Permanent Candidate List having been determined for reasons of committing acts. other crimes. This research is normative legal research with a statutory approach and a conceptual approach. Starting from these different legal interpretations, the author conducted normative juridical research regarding the legal interpretation of the provisions of Article 87 Paragraph (1) letter d General Election Commission Regulation No. 10 of 2023 concerning Nominations of Members of the People's Representative Council, Provincial Regional People's Marriage Council and Regency/City Regional People's Marriage Council regarding the constitutional rights of citizens to become legislative candidates in the 2024 elections